The therapeutic potential of resistant starch in modulation of insulin resistance, endotoxemia, oxidative stress and antioxidant biomarkers in women with type 2 diabetes: a randomized controlled clinical trial - Karimi, Pouran; Farhangi, Mahdieh Abbasalizad; Sarmadi, Bahareh; Gargari, Bahram Pourghassem; Javid, Ahmad Zare; Pouraghaei, Mahboob; Dehghan, Parvin (Karger, 2016)
Aims: This trial aims to determine the effects of resistant starch (RS) subtype 2 (RS2) on glycemic status, metabolic endotoxemia and markers of oxidative stress. Methods: A randomized, controlled, parallel-group clinical trial group of 56 females with type 2 diabetes mellitus (T2DM) was divided to 2 groups. The intervention group (n = 28) and control group (n = 28) received 10 g/day RS2 or placebo for 8 weeks, respectively. Fasting blood samples were taken to determine glycemic status, endotoxin, high sensitivity C-reactive protein (hs-CRP), malondialdehyde (MDA), total antioxidant capacity (TAC), antioxidant enzymes concentrations as well as uric acid at baseline and after the intervention. Results: After 8 weeks, RS2 caused a significant decrease in the levels of MDA (-34.10%), glycosylated hemoglobin (-9.40%), insulin (-29.36%), homeostasis model of insulin resistance (-32.85%) and endotoxin (-25.00%), a significant increase in TAC (18.10%) and glutathione peroxidase (11.60%) as compared with control. No significant changes were observed in fasting plasma glucose, quantitative insulin sensitivity check index, hs-CRP, superoxide dismutase, catalase and uric acid in the RS2 group as compared with the control group. Conclusion: Supplementation with RS2 may be improved glycemic status, endotoxemia and markers of oxidative stress in patients with T2DM.